Everyday life and Identity in the Clinic of Activity and Ergology - Naujorks, Carlos José (2018)
This article addresses the presence the concepts of everyday life and identity in the approaches usually designated Clinic of Activity and Ergology and propose an analysis of the methodological relevance of this concepts to research of daily work situations. It is argued that although the concepts in question are not key concepts in the theories under analysis, they present fundamental aspects of these approaches. The Work Clinics, in general, and the approaches here considered in particular, are based on a distinction between the prescribed and actual dimensions of the work, including the activity as the possibilities of action of the subject who works opposite the prescribed amount of work and the various elements that make up the work processes and the organizational context. By highlighting the importance of everyday notions and identity, it is intended to contribute both to the theoretical development of clinical work studies and to their intervention methodologies.